PERANAN INFORMASI AKUNTANSI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN BAHAN BAKU - Abdul Rahman, Mulyadi (Fakultas Ekonomi Universitas Muhammadiyah Aceh, 2011)
Mulyadi AR (Dosen Fakultas Ekonomi Universitas Muhamaddiyah Aceh) ABSTRACT Management accounting information presented in very powerful company in purchasing raw materials. Raw materials can be used optimally in accordance with the criteria and in accordance with be existing data, the reports on the use of raw materials accounting period of the previous management. Inventories of raw materials can be compared to the use of which has been budgeted so that the production process can run continuously. Key words : information, accounting, management, raw material DAFTAR PUSAKA Ahyari, Agus, (19985). Management Produksi : Pengendalian Produksi, Yogyakarta: BPFE. Anthony, Robert.N.Deardent Jhon, and Vijai Govindaraja, (1992). Manajemen Control Sistem, Seventh Edition, Tokyo: Topan Company. Handoko, T. Hani, (1993). Dasar-Dasar Manajemen Produksi dan Operasi, Yogyakata: BPFE. Mulyadi, (1993). Akuntansi manajemen: Kosep manfaat dan Rekayasa, Edisi 2, Yogyakarta: BPSTIE-YKPN Supriyono, RA., (1991). Akuntansi Manajemen 2: Struktur Pengendalian Manajemen, Yogyakarta: BPSTIE-YKPN. —————–, (1993). Akuntansi manajemen I,: Konsep Dasar Akuntansi Manajemen dan Proses Perencanaan, Yogyakarta: BPFE. Wilson, James D, And John B. Cample, (1991). Controllership, Tugas Akuntan Manajemen Terjemahan: Tjintjin Fenix Tjendra Edisi Ketiga, Jakarta: Penerbit Erlangga.